Ensuring multidimensional equality in public service - Akoluk, Damla; Karsu, Özlem (Socio-economic planning sciences, 2022)
Service planning problems typically involve decisions that lead to the distribution of multiple benefits to multiple users, and hence include equality and efficiency concerns in a multidimensional way. We develop two mathematical modeling-based approaches that incorporate these concerns in such problems. The first formulation aggregates the multidimensional efficiency and equality (equitability) concerns in a biobjective model. The second formulation defines an objective function for each benefit, which maximizes the total social welfare obtained from that specific benefit distribution; this results in an n-objective model, where n is the number of benefits. We illustrate and compare these approaches on an example public service provision problem. •We consider optimization problems to allocate multiple benefits to multiple users.•We propose two multi-objective models to deal with equity and efficiency concerns.•We demonstrate the use of the approaches on a public education planning problem.•The results show the benefits of considering equality in public service planning.